Pengaruh Brand Ambassador terhadap Keputusan Pembelian dengan Citra Merek sebagai Variabel Intervening (Kasus Produk Skincare Whitelab pada Masyarakat di Yogyakarta) - Margaretha Olivia Putri; Sri Ekanti Sabardini (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to analyze the influence of Brand Ambassador on Purchase Decisions with Brand Image as an Intervening variable. Samples were taken by non-probability sampling method with purposive sampling technique. The number of samples in this study were 100 people who were consumers who had purchased at least once and used Whitelab Skincare products in Yogyakarta and were at least 12 years old. Primary data were collected using a questionnaire technique. Data analysis was performed using multiple linear regression method. Before the regression was carried out, the instruments were tested, namely validity and reliability tests, data normality tests, and classical assumption tests which included multicollinearity tests, heteroscedasticity tests. Hypothesis testing is done by t test and Sobel test. The results of the study show that Brand Ambassador has a significant positive effect on Brand Image, Brand Ambassador has a significant positive effect on Purchase Decisions, Brand Image has a significant positive effect on Purchase Decisions, and there is a positive and significant influence of Brand Ambassador on Purchase Decisions with Brand Image as an Intervening variable.